Expression of the major and pro-Oncogenic H3K9 lysine methyltransferase SETDB1 in non-Small cell lung cancer (2019)
SETDB1 is a key histone lysine methyltransferase involved in gene silencing. The SETDB1 gene is amplified in human lung cancer, where the protein plays a driver role. Here, we investigated the clinical significance of SETDB1 expression in the two major forms of human non-small cell lung carcinoma (NSCLC), i.e., adenocarcinoma (ADC) and squamous cell carcinoma (SCC), by combining a meta-analysis of transcriptomic datasets and a systematic review of the literature. A total of 1140 NSCLC patients and 952 controls were included in the association analyses. Our data revealed higher levels of SETDB1 mRNA in ADC (standardized mean difference, SMD: 0.88; 95% confidence interval, CI: 0.73–1.02; p < 0.001) and SCC (SMD: 0.40; 95% CI: 0.13–0.66; p = 0.003) compared to non-cancerous tissues. For clinicopathological analyses, 2533 ADC and 903 SCC patients were included. Interestingly, SETDB1 mRNA level was increased in NSCLC patients who were current smokers compared to non-smokers (SMD: 0.26; 95% CI: 0.08–0.44; p = 0.004), and when comparing former smokers and non-smokers (p = 0.009). Furthermore, the area under the curve (AUC) given by the summary receiver operator characteristic curve (sROC) was 0.774 (Q = 0.713). Together, our findings suggest a strong foundation for further research to evaluate SETDB1 as a diagnostic biomarker and/or its potential use as a therapeutic target in NSCLC.